Some Remarks on Contemporary West-Slavic kynonymy - Kołodziej, Agnieszka (Poznańskie Studia Slawistyczne, 2022)
This article investigates kynonyms, which constitute one of the most prominent categories of zoonyms. The research material was obtained with the use of an 11-point survey and encompasses the West-Slavic languages: Polish, Czech and Slovak. The study aims to indicate the core tendencies in how dogs are named in these languages, as well as potential regularities or inconsistencies therein. The article encompasses a theoretical component, a discussion on terminology and an exploration of the research material (through semantic and formal means). Most kynonyms are created through the use of: names or surnames of fictional characters known from television and films; pragmatic names; and a characteristic of the animal itself. Only approximately 6.5% of the research material includes the names derived through word formation; the other names involve metaphorical references. The study also incorporates a stratification of the dog’s image; however, the only correlation uncovered was the relationship between the race of the dog (small or large) and the type of accommodation in which that dog stayed.